APPLICATION OF AHP AND MABAC METHODS IN THE FRAMEWORK OF MULTI-CRITERIA DECISION-MAKING IN THE SELECTION OF INVESTMENT PROJECTS - Đoković, Lazar; Doljanica, Dragan (Journal of process management and new technologies, 2023)
A multi-attribute decision-making process and ranking of investment projects is almost inevitable today in order to realize and achieve an investment project. We can observe the given process from the aspect of decision theory. Today, it is unthinkable to make a decision on the acceptance of an investment project, without looking at different criteria, the only option is to set the choice of an investment project as a multi-attributive decision-making problem. The goal of this paper is to present a multi-attribute decision-making model, when we have several proposed investment projects and when I want to evaluate the given projects and just rank them for choosing the best method. Based on its wide application, the AHP method will be used to determine the weights of the criteria themselves during the decision-making process, while the MABAC method will be used for the further process of ranking investment projects in order to obtain a single-investment ranking of proposed alternatives, more precisely, proposed investment projects.
Keywords: multi-attribute decision making; investment projects; AHP method; MABAC method